Effect of ZnO Nanoparticles on Brassica nigra Seedlings and Stem Explants: Growth Dynamics and Antioxidative Response - Zafar, Hira; Ali, Attarad; Ali, Joham S.; Haq, Ihsan U.; Zia, Muhammad (Frontiers in Plant Science, 2016)
Nanoparticles (NPs) have diverse properties in comparison to respective chemicals due to structure, surface area ratio, morphology, and reactivity. Toxicological effects of metallic NPs to organisms including plants have been reported. However, to the authors’ knowledge there is no report on the effect of NPs on in vitro culture of plant explants. In this study, ZnO NPs at 500-1500 mg/L badly affected Brassica nigra seed germination and seedling growth and raised antioxidative activities and antioxidants concentrations. On the other hand, culturing the stem explants of B. nigra on Murashige and Skoog (MS) medium in presence of low concentration of ZnO NPs (1-20 mg/L) produced white thin roots with thick root hairs. At 10 mg/L ZnO NPs shoots emergence was also observed. The developed calli/roots showed 79% DPPH (2,2-diphenyl-1-picryl hydrazyl) radical scavenging activity at 10 mg/L. While total antioxidant and reducing power potential were also significantly different in presence of ZnO NPs. Non enzymatic antioxidative molecules, phenolics (up to 0.15 µg GAE/mg FW) and flavonoids (up to 0.22 µg QE/mg FW), also raised and found NPs concentration dependent. We state that ZnO NPs may induce roots from explants cultured on appropriate medium and can be cultured for production of valuable secondary metabolites.